Adiponectin level in diabetic kidney disease the relationship with glycemic control and microvascular complications; a mystery unresolved - A. E. Tony, Effat; H.Mostafa, Mohamed; F. Abdelaal, Refaat; A. Tony, Abeer; El- Shereif, Tahra; Adel A. Abdou, Madleen (International Journal of Medicine, 2018)
Background: Defining new predictive biomarkers in diabetic kidney disease (DKD) would provide a window of opportunity for preventive and/or therapeutic interventions to prevent or delay the onset of irreversible long-term micro and or macro vascular complications. Adiponectin (ADPN) has been variously associated with diabetic microvascular complications; however, no comprehensive clinical data exist examining the association between adipocytokines and the presence of these complications.Aim of study: we aimed to measure the plasma levels of adiponectin in patients with type 2 diabetes mellitus, to assess whether these levels vary with the different stages of DKD according to their e GFR and to evaluate its relation to their microvascular complications and glycemic control.Methods: This is a prospective observational study including 100 T2DM classified into two groups according to their albuminuria levels and estimated GFR. Participants subjected to thorough history taking and clinical examination. Serum level of ADPN was assessed in all patients.Results: Serum ADPN levels were significantly lower in T2DM patients with nephropathy (P = 0.001), while their levels were non-significantly higher in patients with non-proliferative retinopathy or neuropathy. Their levels were lowered with more advanced stages of DKD with nephropathy and the decrement was dependent on their severity (P<0.001). Levels of ADPN with cutoff value of < 22600 (Î¼g/mL) had ability to diagnose microvascular complications in our diabetic patients with sensitivity (81%) and specificity (27%). Multivariate logistic regression analysis showed that the odds ratio for the presence of nephropathy in the lowest tertile of ADPN was 1.09 (95% CI; 11.45- 13.08, P= 0.06), therefore, ADPN was not an independent risk factor for diabetic nephropathy. However, its higher level was independently associated with increased odds for the presence of neuropathy in particular. Conclusions: ADPN plays a role in the pathogenesis of microvasculopathy in diabetic patients and help to identify high-risk patients and modulate the therapeutic potential in the prevention of DKD.Â Â